Do “monstro” ao homem: motivos de violências contra a mulher - Silva, Carla da (2020)
The objective of this study is to analyze and understand the motivations that lead men to practices of violence against women in the domestic sphere. With the priority of listening to men, allowing them to tell their version of the facts (of the violence), their context and reality, as well as, their analysis of the reasons that drove them to the acts and their “general” view of the violence committed against the woman. We also listened to the professionals who serve this audience, with the aim of reflecting on the mode of intervention practiced and their perception of the reasons that lead men to commit violence against women. We understand man as a product and producer of relationships, therefore, we assume in this work the terminology of the author of violence, as well as the deconstruction of the aggressor and dominator for an ordinary man. The experiences with violence will be presented in a multidimensional perspective, understanding that reality and the social context are dynamic and diverse, as well as the human complexity that moves between objective and subjective, between abstract and concrete, between reason and emotion. To this end, we conducted a qualitative research, centered on the testimonies of men who committed violence against women and the professionals who work with these subjects. The results obtained in the study pointed out several reasons, inserted in the objective field: traditional family; macho culture; the stories experienced with violence and its (re) production and, in the subjective field: love, hatred, jealousy, lack of control, together drive violent acts, violence being used as an instrument first in the absence of resources of affection and dialogue. The professionals pointed out that the reflection group and listening, present positive results in the speech of men, therefore, the perpetrators of violence cannot be reduced to the facts present in the police report, but it is necessary to look beyond the facts, consider the social context and the subjective resources involved. Building intervention strategies that address both fields: objective and subjective, with non-violent resources